Trends in hospitalizations due to motorcycle accidents involving men aged 20 to 39 years in the state of Santa Catarina - Southern Brazil - Ione Jayce Ceola Schneider; Marcelo Vargas Schütz; Nazaré Otília Nazário; Ameg Dalpiaz; Alexandre Márcio Marcolino; Rafael Inácio Barbosa (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2017)
Abstract Introduction Motorcycles accidents are responsible for most of the injuries due to external causes and consequent high hospitalization rates. Objective This study aimed to analyze the temporal trend in motorcycle accident morbidity among young male adults in the State of Santa Catarina. Methods This is an ecological study on motorcycle accident morbidity in men aged 20 to 39 years in the State of Santa Catarina between 1998 and 2012. Data from the Hospital Information System of the Brazilian Unified Health System were used in the study. Specific hospital morbidity rates adjusted for age, age group and geographical region, were calculated to analyze the temporal trend in the State through regression model estimates obtained using the Joinpoint program. Results A total of 19.889 hospital admissions for motorcycle accidents occurred in the State of Santa Catarina in the period studied, with a significant increase of 10.9% per year. In the studied age groups, the 20-29 year old group increased 9.7% per year, whilst the 30-39 year old group increased 13.7%. Except for Foz do Rio Itajaí, all geographical regions of the state showed a significant increase of morbidity. Conclusion There has been an increasing trend of morbidity for motorcycle accidents in State of Santa Catarina. These results show the need for improvement of policies to reduce the causes of this type of accident.